Measurement of the inclusive charmless semileptonic branching fraction of beauty hadrons and a determination of |Vub| at LEP - Dova, María Teresa (1998)
A measurement of the inclusive charmless semileptonic branching fraction of beauty hadrons, b→Xuℓν, has been performed using almost two million hadronic Z decays collected by the L3 experiment at LEP, yielding the result: Br(b→Xuℓν)=(3.3±1.0±1.7)×10−3. The first uncertainty is statistical and the second is systematic. The modulus of the Cabibbo-Kobayashi-Maskawa matrix element Vub extracted from this measurement is: <mtext>|</mtext><mtext>V</mtext>ub<mtext>|=(6.0</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace>+0.8−1.0<mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace>+1.4−1.9<mtext>±0.2)×10</mtext>−3<mtext>,</mtext> where the uncertainties are statistical, systematic and theoretical, respectively.